2008
DOI: 10.1111/j.1467-8624.2008.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Limitations on Reliability: Regularity Rules in the English Plural and Past Tense

Abstract: Two studies investigated 3-to 5-year-olds' trust in a reliable informant when judging novel labels and novel plural and past tense forms. In Study 1, children (N=24) endorsed the names of new objects given by an informant who had earlier labeled familiar objects correctly over the names given by an informant who had labeled the same objects incorrectly. In Study 2, children (N = 24) endorsed novel names given by an informant who had earlier expressed the plural of familiar nouns correctly over one who had expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…Consistent with previous research on acceptance of informant testimony by 3-to 5-year-olds (e.g., Jaswal, McKercher, & VanderBorght, 2008;Nurmsoo & Robinson, 2009a, 2009b, there were no significant age differences in response patterns. The majority of children in each age group exhibited the positivity bias pattern, and a substantial minority showed the reliability response pattern.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous research on acceptance of informant testimony by 3-to 5-year-olds (e.g., Jaswal, McKercher, & VanderBorght, 2008;Nurmsoo & Robinson, 2009a, 2009b, there were no significant age differences in response patterns. The majority of children in each age group exhibited the positivity bias pattern, and a substantial minority showed the reliability response pattern.…”
Section: Discussionsupporting
confidence: 90%
“…As suggested earlier, a number of studies have shown that 3- to 5-year-olds can quickly learn to discount information from a consistently inaccurate speaker (e.g., Birch et al, 2008; Jaswal & Neely, 2006; Jaswal et al, 2008; Koenig et al, 2004). In the current study, however, toddlers did not become more skeptical of E2’s testimony despite his repeated errors: In their post-testimony responses, they instructed E1 to search in the gravity location indicated by E2, on average, 63% ( SD = 36%) of the time on the first three trials, and 61% ( SD = 37%) of the time on the last three trials.…”
Section: Resultsmentioning
confidence: 83%
“…A number of recent studies have shown that preschool-aged children are more likely to trust novel information from an individual who has been correct in the past rather than one who has been incorrect (e.g., Birch, Vaultier, & Bloom, 2008; Jaswal & Neely, 2006; Jaswal, VanderBorght, & McKercher, 2008; Koenig, Clement, & Harris, 2004). Thus, also of interest will be whether over the course of several trials, toddlers will stop trusting unexpected testimony from a speaker who has always been incorrect.…”
Section: Studymentioning
confidence: 99%
“…Jaswal, McKercher, and VanderBorght (2008), for instance, found that children endorsed novel labels from a previously accurate labeler, but did not endorse her irregular plural or past tense forms of novel nouns and verbs; instead, they endorsed regular plural or past tense forms of the novel nouns and verbs, even when they were provided by an unreliable source. In an additional experiment, informant reliability was established by a speaker's consistent use of correct or incorrect morphology.…”
Section: Children's Treatment Of Grammatical Errorsmentioning
confidence: 95%